Allergen skin test reactivity in adult bronchial asthmatic patients - Parveen, T; Nargis, W; Choudhury, AMAR; Karim, R; Begum, N (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13530 JAFMC Vol.8(1) 2012 pp.02-05